Effects of prenatal multiple micronutrient supplementation on growth and cognition through 2 y of age in rural Bangladesh: the JiVitA-3 Trial. Issue 4 (7th September 2016) - Christian, Parul; Kim, Jeongyong; Mehra, Sucheta; Shaikh, Saijuddin; Ali, Hasmot; Shamim, Abu Ahmed; Wu, Lee; Klemm, Rolf; Labrique, Alain B; West, Keith P
ABSTRACT: Background: Childhood undernutrition may have prenatal origins, and the impact of prenatal interventions on postnatal growth is not well known. Objective: We assessed the effects of prenatal multiple micronutrient (MM) supplementation on child growth and cognitive development. Design: In a cluster-randomized controlled trial in rural Bangladesh, prenatal MM supplementation compared with iron-folic acid (IFA) supplementation was examined for its impact on growth assessed longitudinally from birth up to 24 mo of age ( n = 8529) and, in a subsample ( n = 734), on cognitive function at 24 mo of age by use of the Bayley scales of infant and toddler development–third edition test. Results: Prevalence of stunting at birth [length for age z score (LAZ): <−2] was 31.9% in the MM and 35.7% in the IFA groups ( P < 0.001); however, LAZ increased during the first 3–4 mo in both groups. With the use of a linear random-effects model, prenatal MM-exposed children sustained a higher mean predicted LAZ of ∼0.10 at 1 and 3 mo and 0.06 at 6 mo of age compared with children in the IFA group. Supplementation reduced the prevalence of stunting at 1 (RR: 0.95; 95% CI: 0.92, 0.98) and 3 (RR: 0.91; 95% CI: 0.88, 0.94) mo of age. Differences between groups were absent by 6, 12, and 24 mo of age, when nearly 50% of children had stunted growth. Ponderal and linear growth velocities were somewhat slower from 3 to 12 mo of age in the MM group than in the IFA group, but not from 12 to 24 mo of age. There was no difference between groups on composite scores of cognition, language, and motor performance at 24 mo of age. Conclusions: In this Bangladeshi trial, maternal pre- and postnatal MM supplementation resulted in improvements in LAZ and reduction in stunting through 3 mo of age, but not thereafter and had no impact on cognitive and motor function at 2 y. This trial was registered at clinicaltrials.gov as NCT000860470.